PROSEDUR PENJUALAN ALAT BERAT (TOYOTA FORKLIFT) PADA PT TRAKTOR NUSANTARA CABANG MAKASSAR - Ahmad Firdaus (Universitas Muhammadiyah Makassar, 2020)
This research paper was identified to measure procedure of sales of Heavy Equepment (Toyota Forklifts) at PT Traktor Nusantara branch Makassar. Furthermore this research used qualitatives descriptive method which described the observations and analyzes data. This research paper was the result of research conducted on 04 May to 25 May 2018. The results showed that the procedure of sale of Heavy Equepment (Toyota Forklifts) at PT Traktor Nusantara branch Makassar was in accordance with SOP (Standard Operational Co mpany). Documents and records used in the transaction of cash and credit sales at Pt Traktor Nusantara Makassar Branch was already effective, it can be seen from the documents and records that are used already complete, from ordering goods, credit, filing receipts, invoice, as well as documents of proof of delivery of the goods. As for the abstacles faced in the process of sale of heavy equipment, namely the process of payments made by the customer is often too late. The goods have arrived at the payout process is not finished